2005
DOI: 10.1007/s00280-005-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium depletion enhances cisplatin-induced nephrotoxicity.

Abstract: This study indicates a substantial additive effect of Mg-depletion on cisplatin induced renal toxicity as evidenced by significant changes in plasma creatinine and urea, renal failure induced mortality and loss of renal transporters. This should give cause for concern since the nephrotoxicity observed during cisplatin treatment might be substantiated by the known Mg-loss associated with cisplatin treatment especially in patients suffering from intense gastro-intestinal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 19 publications
2
52
0
3
Order By: Relevance
“…The study on Mg-depleted female rats treated with CP (2.5 mg/kg once weekly for 3 weeks) revealed an almost complete disappearance of Na,K-ATPase (alpha-subunit), Na/H-exchanger, and Na,K,2Cl-cotransporter, suggesting a dramatic synergistic effect of CP and Mg depletion on renal function including the expression pattern of outer medullary Na transporters (5). Our data did not show CP-caused changes in 24-h urinary Mg or 24-h K excretion in rats of both genders treated with CP (2.5 mg/kg once a day for 3 days).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study on Mg-depleted female rats treated with CP (2.5 mg/kg once weekly for 3 weeks) revealed an almost complete disappearance of Na,K-ATPase (alpha-subunit), Na/H-exchanger, and Na,K,2Cl-cotransporter, suggesting a dramatic synergistic effect of CP and Mg depletion on renal function including the expression pattern of outer medullary Na transporters (5). Our data did not show CP-caused changes in 24-h urinary Mg or 24-h K excretion in rats of both genders treated with CP (2.5 mg/kg once a day for 3 days).…”
Section: Discussionmentioning
confidence: 99%
“…paštas: donatasstakisaitis@vvkt.lt solution 50 mg/100 mL, Ebewe Pharma Ges.m.b.H., A-4866 Unterach, Austria) into the caudal vein (once a day for 3 days) were examined. This dose was chosen in accordance with the literature data on preclinical CP pharmacodynamics (5).…”
Section: Methodsmentioning
confidence: 99%
“…Hypomagnesemia reduces the expression of certain transporters in renal tubules in order to maintain serum Mg concentrations. This reduction in tubular transporters also amplifies the renal accumulation of cisplatin, which is accompanied by further nephrotoxicity (20)(21)(22). In this vicious cycle, we hypothesize that Mg supplementation protects against nephrotoxicity by blocking the augmented accumulation of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Large amounts of hydration with saline, mannitol and furosemide are accepted as the standard of care for patients treated with regimens containing high-dose (≥60 mg/m 2 ) cisplatin (3,10,11). Previous studies have demonstrated that Mg supplementation also confers protective effects against cisplatin-induced nephrotoxicity (10,(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesemia was observed in humans (28) and in experimental animals (29). It was reported that in cisplatin-treated mice the urinary magnesium waste almost doubled (30), and the magnesium depletion was shown to enhance cisplatin nephrotoxicity (31). Magnesium is known to be a critical cofactor in many cellular enzyme processes including membrane transport and cellular repair (32).…”
Section: Discussionmentioning
confidence: 99%